HIGH-PRESSURE ALLOYING OF IRON AND XENON: "MISSING" XE IN THE EARTH'S CORE? - Lee K.K.M.; Steinle-Neumann G. (My University, 2006)
Ab initio quantum mechanical calculations show that xenon (Xe) can be alloyed with hexagonal close-packed iron at high pressure through substitutional incorporation, with a favorable enthalpy of formation for the alloy relative to the separate elemental solids, suggesting that Xe is soluble in the Earth's iron-rich core (up to ~0.8 mol%). This alloying behavior and the possible presence of a significant amount of Xe in the core are important for understanding the accretion and evolution of the Earth and its atmosphere. Copyright 2006 by the American Geophysical Union.